PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG HYPNOBIRTHING DI RUMAH SAKIT WULANDARI - HELMI WARDAH NASUTION (JURNAL ILMIAH KOHESI, 2020)
Counseling can increase the knowledge of pregnant women about hypnobirthing as an effort to use hypnosis to get asmooth, safe and comfortable delivery. Data from Pratama Vina Medan Clinic in 2018, the number of pregnant women fromJanuary to April is 60 people, including 30 people entering the third trimester of pregnancy. The number of women givingbirth was 15 people with a normal delivery of 10 people,and a long parturition of 5 people. The purpose of the study was todetermine the effect of counseling on knowledge and attitudes of pregnant women about hypnobirthing at Rumah SakitWulandari Medan. This type of research is a quasi experiment with the design of one group pre test and post test designcarried out in August 2018. The population is pregnant women who visited 40 people and all of them were used as researchsamples. Collecting using questionnaires and analyzed using paired sample t test on the significance limit α = 0.05.The results showed that there was an influence of counseling on the knowledge of pregnant women about hypnobirthing pvalue 0.037 <0.05 and there was an influence of counseling on the attitude of pregnant women about hypnobirthing p value0.014 <0.05. It is recommended that the Clinical Leaders provide health education about hypnobirthing regularly with othermethods to improve the knowledge and attitudes of pregnant women. Health workers can provide brochures and leaflets asa source of health information to mothers who are supported.